4th Industrial Revolution: The Beginning of Imagination Age - Ashik, Syod Ahsanul Islam; Afroje, Sahariya; Hossain, Nazmul (Advances in Social Sciences Research Journal, 2023)
We are in the everchanging global arena. In the modern global world every sphere including, economy, education, eco-system, social, financial, commercial, industrial as well as political sectors are being changes rapidly, mainly due to technological advertisement, and adaption of changing pattern of technology. Technology has taken the toll in industrial and commercial sector which changing all areas from operation, management, manufacturing, processing to delivery activities. The dramatic changes in this area is called 4th industrial revolution or Industry 4.0 which created revolutionary economic changes and created huge impacts both in developed and developing countries due to globalization of economic affairs and global market economy. The objective of the study is to assess the global trends toward Industry 4.0, its impacts on global economy, and recommendation how developing and list developed countries can keep up pace with the global trend with minimum resources (Physical capital & Human capital). The study is mainly based on secondary sources of data including scholarly journals, articles, books, research materials, news of media outlets and other relevant sources pertaining to the subject. The finding of the study will contribute to understand the Industry 4.0, its framework and function, its challenges and opportunities, and way for developing and list developed countries to come to Industry 4.0 platform.